FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PEKERJA PRODUKSI CETAKAN KEMASAN PLASTIK DI PT X TAHUN 2023 - Nurisma Handayani (2023)
The accident in company X's plastic packaging injection mould production workers was thought to be due to work fatigue stemming from two factors, namely individual and work factors such as lifting heavy and slippery processed materials. Therefore, to prevent the next accident, further research is needed. This study aims to determine factors related to work fatigue in plastic packaging mold production workers at PT X in 2023. This research was a cross-sectional design, with population of this study consisted of 73 workers, and 69 workers as samples were selected using a purposive sampling technique. Data collection used questionnaires (SOFI and PSQI) and direct measurements (weight scales and stature meters). Data were analyzed bivariately using chi-square test. Analysis of result shows that variables with significant relationship for work fatigue are age (p-value = 0.043), sleep quality (p-value = 0.010), smoking habits (p-value = 0.003), years of service (p-value = 0.003), heavy category workload (p-value = 0.022), and working time (p-value = 0.004). Meanwhile, nutritional status (p-value = 0.754) was unrelated to work fatigue. For recommendations, workers needs to improve their healthy lifestyle, such as slowly reducing cigarette consumption, work according to the body's ability, and optimizing the use of assistive devices.